Optimalisasi Pengelolaan Sumber Daya Manusia Dalam Mendukung Peningkatan Kinerja Pelayanan - Ridwan Hakiki; Endang Syarif; Asep Saeful Falah; Wiby Wibawa; Firgie Guliva (CV. SINAR HOWUHOWU, 2025)
Human resource management plays a crucial role in improving service performance at the village level. Sindangmukti Village, Panumbangan District, Ciamis Regency, has considerable human resource potential; however, its management has not yet been fully implemented based on systematic human resource management principles. Several challenges are identified, including unclear division of tasks and responsibilities, weak work coordination, and low levels of discipline and accountability among village officials and activity implementers. This community service activity aims to optimize human resource management to support the improvement of service performance in Sindangmukti Village. The methods employed include human resource needs assessment, human resource management training, mentoring in the implementation of work systems, and evaluation of service performance. The expected outcomes of this activity are improved understanding and skills of village human resources in managing their duties, enhanced service performance, and the establishment of more effective and sustainable village governance.